Recent Apolipoprotein CIII trials. Issue 6 (28th December 2022) - Tramontano, Daniele; Bini, Simone; D'Erasmo, Laura; Arca, Marcello
Abstract : Purpose of review: This review will briefly revise the evidence concerning the pharmacological inhibition of Apolipoprotein CIII (ApoCIII) in patients with hypertriglyceridemia. Recent findings: ApoCIII is a plasma apolipoprotein playing a major role in the metabolism of triglyceride-rich lipoproteins, namely chylomicrons and very-low-density lipoproteins as well as in the pathological processes involved in atherosclerosis. Therefore, ApoCIII is a potential new target for reducing plasma levels of TRLs and, thereby, cardiovascular risk. In recent years, there have been extensive preclinical and clinical pharmacological studies aimed at testing drugs directed against ApoCIII. Summary: In this review, firstly we will summarize the molecular function of ApoCIII in lipoprotein metabolism. Then, we will examine the lipid-lowering potential of the pharmacological inhibition of ApoCIII based on the results of clinical trial employing Volansesorsen, the first approved antisense therapeutic oligonucleotide against ApoCIII mRNA. The future perspectives for ApoCIII inhibition will be also revised.